2019
DOI: 10.1016/j.ajpath.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin

Abstract: The complex relationship between diet and metabolism is an important contributor to cellular metabolism and health. Over the past few decades, a central role for mammalian target of rapamycin (mTOR) in the regulation of multiple cellular processes, including the response to food intake, maintaining homeostasis, and the pathogenesis of disease, has been shown. Herein, we first review our current understanding of the biochemical functions of mTOR and its response to fluctuations in hormone levels, like insulin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…The active form of PDK1 then triggers the phosphorylation of protein kinase B (Akt) [ 28 ]. Afterward, the phosphorylated Akt enhances the levels of the mammalian target of rapamycin (mTOR) phosphorylation, resulting in food intake reduction [ 29 ]. The potential molecular mechanisms of the anorexigenic action of insulin are depicted in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The active form of PDK1 then triggers the phosphorylation of protein kinase B (Akt) [ 28 ]. Afterward, the phosphorylated Akt enhances the levels of the mammalian target of rapamycin (mTOR) phosphorylation, resulting in food intake reduction [ 29 ]. The potential molecular mechanisms of the anorexigenic action of insulin are depicted in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in elderly people mTOR may show the beneficial outcomes of its activity, preventing sarcopenia and lean mass loss. In conclusion, there is a general consensus that this kinase can promote metabolic health or disease depending on human age and on particular signaling of specific tissues [ 72 ].…”
Section: Nutrient Sensors That Potentially Affect Health Spanmentioning
confidence: 99%
“…Moreover, gene expression studies for intramuscular fat in pig identified differentially expressed genes such as RTF1 in OCU17 (Damon et al, 2012) and SLC24A2 in OCU1 (Li et al, 2010). RRGA and RPS6 in OCU1 could stimulate the lipogenesis and the lipid accumulation via activation of the mTOR signalling pathways (Wipperman et al, 2019). PLA2G4B in OCU17 is linked to phospholipid catabolic processes because of its phospholipase A2 (PL2) activity.…”
Section: Underlying Selected Genes and Gene Ontology Terms For Divergmentioning
confidence: 99%